The A-G polymorphism in exon 1 of the CTLA-4 gene is not associated with systemic lupus erythematosus. - Heward, J; Gordon, C; Allahabadia, A; Barnett, A; Franklyn, J; Gough, S (1999)
OBJECTIVES: Factors contributing to the development of systemic lupus erythematosus (SLE) remain largely unknown although are likely to include both environmental and genetic components. Studies on murine lupus have indicated a role for an antibody that blocks binding of cytotoxic T lymphocyte associated-4 (CTLA-4) to B7 on antigen presenting cells in the treatment of disease, suggesting that CTLA-4 may play an important part in the disease process. This study, therefore, investigated the frequency of a previously described A-G polymorphism in exon 1 of the CTLA-4 gene, the G allele of which has shown to be associated with both Graves' disease and type I diabetes, to determine whether this polymorphism was playing a part in the development of SLE. METHODS: One hundred and twenty six SLE patients and 363 control subjects were genotyped for the A-G polymorphism in exon 1 of the CTLA-4 gene. Target DNA was amplified using the polymerase chain reaction and the resulting product was digested using the BbvI restriction enzyme. RESULTS: No differences in allele or genotype frequencies were observed between patients with SLE and control subjects. CONCLUSION: These data suggest that the A-G polymorphism in exon 1 of the CTLA-4 gene does not play a part in the genetic susceptibility to the development of SLE.